CDK4/6 inhibition in low burden and extensive metastatic breast cancer: summary of an ESMO Open—Cancer Horizons pro and con discussion - Awada, Ahmad (ESMO Open, 2019)
In December 2017, ESMO Open—Cancer Horizons convened a round-table discussion on the background and latest data regarding cyclin-dependent kinase (CDK)4/6 inhibitors with endocrine therapy (ET) in the treatment of endocrine-sensitive breast cancer (BC). A review on this discussion was published in summer 2018 (https://esmoopen.bmj.com/content/3/5/e000368). Endocrine-sensitive BC with non-visceral disease and limited spread of the metastases. Endocrine-sensitive BC with non-life-threatening visceral involvement. Several open questions were identified, which led to a second ESMO Open Endocrine-sensitive BC with non-visceral disease and limited spread of the metastases. Endocrine-sensitive BC with non-life-threatening visceral involvement. Regarding scenario 1, the panel agreed that CDK4/6 inhibitors should be recommended in first-line therapy for most patients if cost and practicality allow. However, the use of single-agent ET with an aromatase inhibitor in the first-line treatment of these patients is still a possibility for a small group of patients with very limited disease, such as one or two bone lesions or limited lymph node involvement. Regarding scenario 2, chemotherapy is the first approach for patients with endocrine-sensitive metastatic BC with life-threatening visceral involvement because of the need for a faster response. The therapeutic approaches for patients with non-life-threatening visceral involvement are still under debate. Nevertheless, CDK4/6 inhibitors are currently the treatment of choice for most patients with a close follow-up of tumour response. A treatment algorithm has been suggested at the round table.